The Islamic Education Strategies in Integrating Salafi Traditions and Modernity - Muhammad Abdul Qahhar; Komaruddin Sassi (Bulletin of Pedagogical Research, 2025)
The integration of the Salaf tradition, which adheres firmly to the Qur'an, Sunnah, and the understanding of the best generation of the ummah (as-Salaf as-Shalih), with the demands of modernity is both a challenge and a necessity in the world of contemporary Islamic education. This study aims to analyze strategies that can be implemented by Islamic educational institutions in harmoniously combining these two poles. The research method used is library research with a philosophical and pedagogical analysis approach. Data were collected from primary and secondary sources such as classical books, modern literature, and related scientific journals. The results of the study identified several key strategies. First, a curricular strategy through curriculum reconstruction that combines naqli (religious) and aqli (general & scientific) knowledge in an integrative, rather than secular, manner. Second, a methodological strategy by implementing learning methods that respect the authority of texts but are packaged with a modern pedagogical approach that is critical, innovative, and in accordance with the psychological development of students. Third, a human resource strategy by developing educators (teachers/ustadz) who have a straight understanding of religion while mastering modern educational science and technology. Fourth, a cultural strategy involves creating an Islamic educational environment while still fostering dialogue with contemporary thought and technological advancements. The conclusion of this research is that the integration of Salafi traditions and modernity in Islamic education is not only possible but also essential to foster a generation of moderate Muslims, one with a strong Islamic identity, noble morals, and the ability to actively contribute and compete in the global arena. A holistic and balanced strategy is key to preventing dichotomies, secularism, or fundamentalism in the education system.